Creative industries work across multiple contexts: common themes and challenges - Hennekam, S.; Bennett, Dawn (Emerald, 2017)
Purpose: The purpose of this paper is to examine the precarious nature of creative industries (CIs) work in Australia, Canada and the Netherlands, with a focus on job security, initial and on-going training and education, and access to benefits and protection. Design/methodology/approach: The paper reports from a largely qualitative study featuring an in-depth survey answered by 752 creative workers in the three locations. Findings: Survey data identified common themes including an increase in non-standard forms of employment and the persistence of precarious work across the career lifespan; criticism of initial education and training with particular reference to business skills; the need for and challenges of life-long professional learning; and lack of awareness about and access to benefits and protection. Respondents also reported multiple roles across and beyond the CIs. Practical implications: The presence of common themes suggests avenues for future, targeted creative workforce research and signals the need for change and action by CIs educators, policy makers and representative organizations such as trade unions. Originality/value: While precarious labour is common across the CIs and has attracted the attention of researchers worldwide, a lack of comparative studies has made it difficult to identify themes or issues that are common across multiple locations. © 2017, © Emerald Publishing Limited.